Which criteria are used to clear patients to return to sport after primary ACL reconstruction? A scoping review. Issue 18 (September 2019) - Burgi, Ciara R; Peters, Scott; Ardern, Clare L; Magill, John R; Gomez, Christina D; Sylvain, Jonathan; Reiman, Michael P
Abstract : Objective: To describe the criteria used to clear athletes to return to sport (RTS) following primary ACL reconstruction. Design: Scoping review. Data sources: MEDLINE, Embase, CINAHL and SPORTDiscus electronic databases were searched using keywords related to ACL and RTS. Eligibility criteria: Prospective or retrospective studies reporting at least one RTS criterion for athletes who had primary ACL reconstruction with an autograft. Results: In total, 209 studies fulfilled the inclusion criteria. RTS criteria were categorised into six domains: time, strength, hop testing, clinical examination, patient-report and performance-based criteria. From the 209 included studies, time was used in 178 studies (85%), and in 88 studies (42%) was the sole RTS criterion. Strength tests were reported in 86 studies (41%). Sixteen different hop tests were used in 31 studies (15%). Clinical examination was used in 54 studies (26%), patient report in 26 studies (12%) and performance-based criteria in 41 studies (20%). Summary: Time and impairment-based measures dominated RTS criteria, despite sport being a complex physical and biopsychosocial activity with demands across all aspects of function. Time was included as a criterion in 85% of studies, and over 80% of studies allowed RTS before 9 months. Whether RTS tests are valid—do they predict successful RTS?—is largely unknown.